SPARKOL VIDEOSCRIBE HISTORICAL ANIMATION VIDEOS TO ENHANCE INTEREST AND LEARNING OUTCOMES OF TENTH GRADE AT MA ASWAJA NGUNUT - Muhammad Khoirul Anam; Joko Sayono; Dewa Agung Gede Agung (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
The present issue in history education is the insufficient utilization of instructional media that could effectively serve as tools for teachers to convey materials to students. Consequently, history lessons in the classroom tend to lack engagement and become monotonous. A viable solution is to implement instructional media that align with the potential and learning characteristics of students at MA Aswaja Ngunut. The required form of instructional media is historical videos based on Sparkol Videoscribe, with a focus on prehistoric site content in Tulungagung. This research and development initiative aims to ascertain the effectiveness of historical video instructional media based on Sparkol Videoscribe in enhancing students' interest and learning outcomes. This research model adapts the ADDIE development model developed by Robert Maribe Branch. The objective of this research is to create a learning media containing prehistoric site content from Tulungagung and to assess the effectiveness of this media on student interest and learning outcomes. Based on the research outcomes, it can be concluded that historical video instructional media based on Sparkol Videoscribe yields valid, effective, practical, and engaging results, leading to increased student interest and learning outcomes. Students' strong preference for audiovisual media is the primary reason for their heightened interest in this product. Therefore, it can be deduced that the product is effective in boosting student interest and learning outcomes.